2008
DOI: 10.1177/0883073808318063
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Cerebellar Injury in Very Low Birth-Weight Infants: 6 Case Reports

Abstract: Cerebellum injury is a severe and underestimated complication in very low birth-weight infants. Six cases of extreme premature babies are reported: 3 of them died during the neonatal period; the other 3 survived with severe neurological disabilities. Microcephaly, strabismus, and severe developmental delay without major motor handicap are very peculiar for the preterm in the long-term outcome. Easy diagnosis is possible by specific ultrasound windows and early diagnosis is required regarding the possible sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Cerebellar injury was detected by neonatal head ultrasound (HUS) [22, 24-26] or on T1/T2-weighted images obtained from a preterm (<36 weeks GA) or a term-equivalent MRI study [9, 22, 26-29]. The severity of CBI varied from small punctate cerebellar hemorrhages (<4 mm) [9, 29, 30] to more severe forms of cerebellar injury including cerebellar infarction and resulting atrophy on conventional MRI [11, 23, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Cerebellar injury was detected by neonatal head ultrasound (HUS) [22, 24-26] or on T1/T2-weighted images obtained from a preterm (<36 weeks GA) or a term-equivalent MRI study [9, 22, 26-29]. The severity of CBI varied from small punctate cerebellar hemorrhages (<4 mm) [9, 29, 30] to more severe forms of cerebellar injury including cerebellar infarction and resulting atrophy on conventional MRI [11, 23, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…14,[35][36][37][38][39][40][41][42] Premature births can interrupt cerebellum growth. Investigation of whether the adverse effect or prematurity on cerebellar dimensions persists after birth has shown smaller cerebellar dimensions in children born prematurely compared to those born at term.…”
Section: Discussionmentioning
confidence: 99%
“…This neural tube subsequently differentiates in the rostral area to form the cerebrum and cerebellum. Development of the cerebellum begins in days [40][41][42][43][44][45], and the fissurae cerebelli and folia cerebelli appear in the cerebellum at the end of the 4th month. The cerebellum is part of the hindbrain, located below the temporal and occipital lobes.…”
Section: Assessment Of Cerebellar Dimensions Usingmentioning
confidence: 99%
“…Cerebellar injury has been increasingly recognized as a characteristic injury of preterm infants. Neuroimaging studies have shown that the cerebellar injuries in preterm infants are correlated with supratentorial lesions, particularly PVL and intraventricular hemorrhage [6][7][8][9][10][11][12][13]. Despite these reports, the impact of cerebellar injury on the development of preterm infant might be under recognized.…”
Section: Introductionmentioning
confidence: 99%